The Human Factor in Mergers, Acquisitions, and Transformational Change. - Rafique, Muhammad (New York : Business Expert Press, 2021)
Balancing theory with practice, this book looks at the financial due diligence, cultural compatibility, and emotional sensitivity at various stages of the M&A and offers a practical process model. Business leaders, change agents, coaching and mentoring practitioners will find the rare combination of great interest.
Cover -- Halftitle -- Title -- Copyright -- Description -- Contents -- Testimonials -- Chapter 1: Introduction -- Chapter 2: Rear-View Mirror Perspective -- Chapter 3: Importance of Understanding and Being Responsive to Emotions -- Chapter 4: Mentoring -- Chapter 5: Coaching in Transformational Change -- Chapter 6: Using Coaching to Embed Training -- Chapter 7: Time-Line Model 1 -- Chapter 8: Time-Line Model 2 -- Abbreviations -- References -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Organizational change; Business planning; Consolidation and merger of corporations; Electronic books